Experimental study of the hormonal composition of the curves of the voltage regulator - Karimov R.Ch., Rasulov A.N., Seytmuratov B.T., Almardonov О. (International Journal of Advanced Science and Technology, 2020)
This article deals with the analysis of power quality indicators when using a volt-add voltage stabilizer, the magnetizing windings of which are switched using contactless voltage relays made on the basis of semiconductor devices, as well as the duration of the transition process when switching an active-inductive load connected to the output of the stabilizer.